Feasibility and safety of ADAPT in acute distal posterior cerebral artery occlusions - Grieb, Dominik; Meila, Dan; Sommer, Christof-Matthias; Schulz, Katharina; Abu-Fares, Omar; Donnerstag, Frank; Schlunz-Hendann, Martin; Lanfermann, Heinrich; Boxberg, Frederik (European journal of radiology, 2023)
Purpose - The direct aspiration first pass technique (ADAPT) is an effective and safe endovascular treatment for distal medium vessel occlusions (DMVO) of the anterior circulation. Clinical experience with ADAPT in the distal posterior circulation, however, is still limited and published data is scarce. In this original work, feasibility, safety and efficacy of ADAPT with distal access catheters (DAC) for treatment of acute distal posterior cerebral artery occlusions (DPCAOs) is evaluated. - Method - All acute ischemic stroke patients between 2017 and 2022 with primary or secondary DPCAOs in the P2 or P3 segment, that underwent thrombectomy of the DPACO using ADAPT with DACs as frontline therapy, were identified. Demographic data, recanalization rates, procedural safety, and clinical outcome were assessed. - Results - Twenty-four patients with primary (n = 6) or secondary (n = 18) DPCAOs (P2: 21/24; P3: 3/24) were included. Median NIHSS score at admission was 14.5 (IQR 9.5). In all cases, the DPCAO could be reached with the DAC. Successful revascularization (DMVO-p-TICI ≥ 2b) with ADAPT was achieved in 79.2% (19/24), including a first pass effect of 62.5% (15/24), leading to complete recanalization (DMVO-p-TICI 3). Median number of passes was 1 (range 1-2). No complications related to distal PCA aspiration thrombectomy occurred. Median NIHSS and mRS scores at discharge were 4 (IQR 8) and 3 (IQR 2), respectively. - Conclusions - ADAPT appears to be feasible, safe and effective for the treatment of acute DPCAOs in the setting of different occlusion patterns. High revascularization rates without procedural complications can be achieved. Further studies are needed to consolidate these results.